Parents’ intent to vaccinate against influenza during the COVID-19 pandemic in two regions in Switzerland (Swiss Medical Weekly, 2021)
AIMS OF THE STUDY The COVID-19 pandemic is likely to overlap with the seasonal influenza epidemic, increasing the risk of overextending the health system capacity in Switzerland. Influenza vaccine uptake has remained low in most countries, including Switzerland. The aim of the study was to determine parents’ intentions towards influenza vaccination of their children, as well as themselves, and to assess regional differences. METHODS Parents presenting to four paediatric emergency departments (Zurich, Bern, Bellinzona, Geneva) were asked to complete an online survey during and after the first lockdown of the COVID-19 pandemic (April to June 2020). The anonymised survey included demographic information, vaccination history and intentions to vaccinate against influenza, as well as attitudes towards future vaccination against COVID-19. RESULTS The majority of children (92%; 602/654) were up-to-date on their vaccination schedule. In 2019/2020, 7.2% (47/654) were vaccinated against influenza. Children with chronic illnesses were more frequently vaccinated than healthy children (19.2% vs 5.6%; p = 0.002). For the coming winter season, 111 (17%) parents stated they plan to vaccinate their children against influenza, more than double the rate from last year, and 383 (59.2%) parents suggested they will vaccinate against COVID-19 once a vaccine is available. Regional differences between “German” and “Latin” Switzerland were found for parents’ intent to have their children vaccinated against influenza next season (Zurich and Bern 14.3%, Bellinzona and Geneva 27.2%, p